THE THERMODYNAMICS AND KINETICS OF URANOPHANE DISSOLUTION IN BICARBONATE TEST SOLUTIONS - Perez I.; Casas I.; Martn M.; Bruno J. (My University, 2000)
The thermodynamic and kinetic properties of a synthetic uranophane (Ca(H3O)2(UO2)2(SiO4)2 . 3H2O) have been determined from dissolution experiments in test solutions of different bicarbonate concentrations at 25°C. The experiments were performed using batch and continuously stirred tank flow-through reactors. From the experimental data obtained with the batch reactor the solubility constant for the reaction: Ca(H3O)2(UO2)2(SiO4)2 . 3H2O + 6H3O+ # Ca+2 + 2UO2+2 + 2H4SiO4 + 11H2O was determined to be log Ks00 = 11.7 +/- 0.6 and the rate equation for the dissolution process is log rdissol (mol s-1 m-2) = -8.3 (+/-0.6) + 0.7 (+/-0.3) log [HCO3-]. By using the continuously stirred tank flow-through reactor we obtained a rate equation in reasonably good agreement with that obtained in the batch reactor: log rdissol (mol s-1 m-2) = -9.2 (+/-0.4) + 0.7 (+/-0.2) log [HCO3-].